Surface Reactivity of Carbonaceous Nanoparticles: The Importance of Surface Pocket - Wang, Hongyu; Chang, Xiaoya; Chen, Dongping (Frontiers in Mechanical Engineering, 2021)
The surface reactivity of carbonaceous nanoparticles was revealed from the barrier height and reaction enthalpy of hydrogen abstraction reaction by H radicals computed at the M06-2X/6-311g(d,p)//B3LYP/6-311G(d,p) level of theory. Small polycyclic aromatic hydrocarbon (PAH) clusters were selected as the model system of carbonaceous nanoparticles. The PAHs considered are naphthalene, pyrene, coronene, ovalene and circumcoronene. Cluster sizes are ranging from dimer to tetramer with a parallel or crossed configuration. All results show similar values as that of monomers, but naphthalene dimers with a crossed configuration yield a lower barrier height and reaction enthalpy by ~2 kcal/mol. A minor size dependence is noticed in the series of naphthalene clusters where a larger cluster yields a smaller barrier height. Larger homogeneous PAH clusters in a size range of 1.1 to 1.9 nm are later generated to mimic nascent soot surface. It is found that the barrier height decreases with the increase of particle size, and the averaged values are ~2 kcal/mol lower than that of monomers. More importantly, a larger particle shows a wider spread in barrier heights, and lower barrier heights are seen in the surface shallow regions (e.g. surface pockets). The lowest barrier height of ~8.5 kcal/mol is observed at a C-H site locating in a surface pocket. A set of model systems were built to reveal the underlying mechanism of reduction in barrier height. It is learnt that the reduction is caused by local interactions between the neighboring atoms and the local curvature. Further analysis using average localized ionization potential shows that larger particles has higher reactivity, further supporting our findings from the barrier height of hydrogen abstraction reactions. Therefore, it is concluded that the surface reactivity depends on the particle size and the most reactive sites always locate at the surface pockets.